Penggunaan Flow Proof pada Perkuliahan Analisis Real untuk Meningkatkan Kemampuan Mahasiswa dalam Menganalisis Pembuktian - Helma Helma (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
Real Analysis is the subjects to help the students in critical thought. Students must have the definitions and theorems to solve the problems and perform a process which is often called the preliminary analysis. After that, students construct the proof based on the preliminary analysis. Based on the characteristics of the problem in Real Analysis, the solution given to the problem is using flow proof in composing preliminary analysis The research shows that the student's ability in analyzing can be improved by using flow proof